Cellular accumulation of the new ketolide RU 64004 by human neutrophils: comparison with that of azithromycin and roxithromycin. - Vazifeh, D (1997)
We analyzed the uptake of RU 64004 by human neutrophils (polymorphonuclear leukocytes [PMNs]) relative to those of azithromycin and roxithromycin. RU 64004 was strongly and rapidly accumulated by PMNs, with a cellular concentration/extracellular concentration ratio (C/E) of greater than 200 in the first 5 min, and this was followed by a plateau at 120 to 180 min, with a C/E of 461 +/- 14.8 (10 experiments) at 180 min. RU 64004 uptake was moderately sensitive to external pH, and activation energy was also moderate (63 +/- 3.8 kJ/mol). RU 64004 was mainly located in PMN granules (about 70%) and egressed slowly from loaded cells, owing to avid reuptake. The possibility that PMN uptake of RU 64004 and other macrolides occurs through a carrier-mediated system was suggested by three key results. First, there existed a strong interindividual variability in uptake kinetics, suggesting variability in the numbers or activity of a transport protein. Second, macrolide uptake displayed saturation kinetics characteristic of that of a carrier-mediated transport system: RU 64004 had the highest Vmax value (3,846 ng/2.5 x 10(6) PMNs/5 min) and the lowest Km value (about 28 microM), indicating a high affinity for the transporter. Third, as observed previously with other erythromycin A derivatives, Ni2+ (a blocker of the Na+/Ca2+ exchanger which mediates Ca2+ influx in resting neutrophils) impaired RU 64004 uptake by PMNs, with a 50% inhibitory concentration of about 3.5 mM. In addition, we found that an active process is also involved in macrolide efflux, because verapamil significantly potentiated the release of all three macrolides tested. This effect of verapamil does not seem to be related to an inhibition of Ca2+ influx, because neither EGTA [ethylene glycol-bis (beta-aminoethyl ether)-N,N',N'-tetraacetic acid] nor Ni2+ modified macrolide efflux. The nature and characteristics of the entry- and efflux-mediating carrier systems are under investigation.